Frequencies of IL-15Rα+ cells in patients with Behçet's disease and the effects of overexpressing IL-15Rα+ on disease symptoms in mice. (October 2018) - Islam, S.M. Shamsul; Choi, Bunsoon; Choi, Juyoung; Lee, Eun-So; Sohn, Seonghyang
Abstract: It has been suggested higher serum levels of IL-15 and lower expression levels of IL-15 receptor alpha (IL-15Rα) are correlated with pathogenesis of Behçet's disease (BD). However, whether overexpressing IL-15Rα could be used as a therapeutic candidate for BD is currently unclear. Therefore, the purpose of this study was to determine whether overexpressing IL-15Rα could affect BD symptoms in a mouse model. IL-15/IL-15Rα complex expressing vector or protein complex of IL-15/IL-15Rα-Fc was used to treat BD mice. Frequencies of IL-15Rα+ cells in peripheral blood leukocytes (PBL) and lymph node cells were determined using a flow cytometer. BD symptoms in mice improved after treatment with IL-15/15Rα expression vector or IL-15/IL-15Rα-Fc protein complex. In addition, treatment with pIL-15/15Rα significantly (p = .016) decreased disease severity score of BD mice compared to treatment with control vector. Frequencies of IL-15Rα+ cells were also significantly (p = .01) higher in peritoneal macrophages of pIL-15/15Rα treated BD mice than those of mice treated with control vector. Frequencies of IL-15Rα+ PBL were also significantly higher in BD mice treated with IL-15/IL-15Rα-Fc protein complex than those in the control group. These results suggest up-regulating IL-15Rα+ cells could be used as novel therapeutic strategies to control BD in the future.